Homomorphisms and Derivations in C*-Algebras - Choonkil Park; Abbas Najati (Abstract and Applied Analysis)
Using the Hyers-Ulam-Rassias stability method of functional equations, we investigate homomorphisms in C*-algebras, Lie C*-algebras, and JC*-algebras, and derivations on C*-algebras, Lie C*-algebras, and JC*-algebras associated with the following Apollonius-type additive functional equation f(z−x)+f(z−y)+(1/2)f(x+y)=2f(z−(x+y)/4).